INTEGRATING THEORY AND PRAXIS IN EMPIRICAL MISSIOLOGY - M. Ehmann (Acta Theologica)
Lectures on contextual theology rightly belong to the standard repertoire of academic training in missiology. While academic lectures on contextual theologies often focus on macro contexts or meso contexts, the concept of the lecture on context analysis at Ewersbach University of Applied Arts strives to focus on the micro context of missionary action. This lecture and the ensuing two-week internship “Missionary social space analysis” take place at the end of the BA programme. This concept leads to an investigation of a concrete micro context, using the methods of empirical social research and social space-oriented action research. The article aims to explore a theory-practice correlation in the training and application of empirical missiology as a practical science in cooperation with an actual local church. The article briefly presents the pedagogical model and the methodology behind this concept and then reflects critically, from a missiological perspective, on the prospects and limits of teaching practical science and action research in the academic setting of a University of Applied Science in Germany and beyond.